2014
DOI: 10.3389/fnagi.2014.00017
|View full text |Cite
|
Sign up to set email alerts
|

One month of contemporary dance modulates fractal posture in aging

Abstract: Understanding the human aging of postural control and how physical or motor activity improves balance and gait is challenging for both clinicians and researchers. Previous studies have evidenced that physical and sporting activity focusing on cardiovascular and strength conditioning help older adults develop their balance and gait and/or decrease their frequency of falls. Motor activity based on motor-skill learning has also been put forward as an alternative to develop balance and/or prevent falls in aging. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 51 publications
1
27
1
3
Order By: Relevance
“…Moreover, it is thought that multi-modal training interventions resemble real-life demands and therefore yield higher chances of successful transfer to other tasks and every-day life situations (Lustig et al, 2009). In line with this, recent studies have highlighted the capacity of lifestyle interventions, like dancing (Kattenstroth et al, 2013; Coubard et al, 2014) or playing video games (Maillot et al, 2012; Pichierri et al, 2012), to enhance sensorimotor and cognitive functions in older adults. Investigating the potential of video games in preventing age-related cognitive decline has gained great research interest within the last years (Green and Seitz, 2015).…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, it is thought that multi-modal training interventions resemble real-life demands and therefore yield higher chances of successful transfer to other tasks and every-day life situations (Lustig et al, 2009). In line with this, recent studies have highlighted the capacity of lifestyle interventions, like dancing (Kattenstroth et al, 2013; Coubard et al, 2014) or playing video games (Maillot et al, 2012; Pichierri et al, 2012), to enhance sensorimotor and cognitive functions in older adults. Investigating the potential of video games in preventing age-related cognitive decline has gained great research interest within the last years (Green and Seitz, 2015).…”
Section: Introductionmentioning
confidence: 84%
“…() found that brief periods of non‐invasive brain stimulation (NIBS) such as transcranial direct current stimulation (tDCS) applied over the primary motor cortex (M1) is capable of evoking short‐lasting behavioral improvements in upper‐extremity tasks required for activities of daily living (Hummel et al ., ; Zimerman et al ., ). Apart from NIBS approaches, several longitudinal training studies have highlighted the capacity of specific lifestyle interventions, such as video game training (Maillot et al ., ; Nicholson et al ., ), nutrition (Witte et al ., ), and dance intervention (Kattenstroth et al ., ; Coubard et al ., ), to prevent the age‐related decline in cognitive and motor function.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underpinning these effects in humans remain unclear but are likely multi-factorial. For example, evidence from in vitro and in vivo studies has revealed a role for DHA in promoting synaptic plasticity [ 15 , 16 , 17 , 18 ] and neurogenesis [ 19 , 20 ]. DHA has also been shown to have a number of neuroprotective effects including suppressing pro-inflammatory pathways and upregulating pro-resolving mediators such as neuroprotectin D1, modulating mitochondrial function and reducing oxidative stress [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, one recent trial revealed that 2.2 g/day n -3 PUFAs for 26 weeks in healthy, cognitively intact older adults resulted in improved performance on executive function tasks [ 12 ]. This finding was associated with improved brain white matter microstructural integrity and gray matter volume measured using fMRI, suggesting the observed effects of n -3 PUFAs on cognition may be related to their upregulating effect on myelination [ 22 ], neurogenesis [ 19 , 23 ] and synaptogenesis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%